Carbon black, sealant comprising the same and its application
Patent Information
- Application Number
- JP2024146592
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-29
- Filing Date
- 2024-08-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0018】 本願発明者は、カーボンブラックが特定の条件を満たすと、カーボンブラック粉末自体の絶縁性が向上するだけでなく、シーラントに適用した場合にも高い絶縁特性を発揮できることを予想外に発見した。
Smart Images

Figure 2025036311000007 
Figure 2025036311000008 
Figure 2025036311000009
Abstract
Description
[Technical field]
[0001] This application claims priority to Taiwan Patent Application No. 112132585, filed on August 29, 2023, the entire text of which is incorporated by reference herein.
[0002] The present disclosure relates to carbon black, and in particular to highly insulating modified carbon black. [Background technology]
[0003] At present, the trend in the development of electronic products is to make them lighter, thinner, and shorter. As electronic products become more miniaturized, the distance between devices also becomes shorter, making the insulating properties of sealants to protect devices more important.
[0004] It is known that sealants are primarily composed of a resin and a hardener. Carbon black can be further added, if desired, to impart color to the sealant and further improve the mechanical properties of the sealant. In the prior art, research into the insulating properties of sealants was focused on the resin used in the sealant without research into other components. As a result, the insulating properties of the sealant were limited by the insulating properties of the resin itself and were difficult to further improve, further limiting the applications of the sealant. Summary of the Invention [Problem to be solved by the invention]
[0005] In view of the above problems, an object of the present disclosure is to provide a sealant having high insulating properties. [Means for solving the problem]
[0006] In order to achieve the above object, the present disclosure provides carbon black that satisfies the following conditions (a) and (b): (a) a nitrogen adsorption specific surface area (NSA) of 0 m 2 / g or greater, 130m 2 / g or less; and (b) an oil absorption of greater than 0 cc / 100 g and less than or equal to 95 cc / 100 g.
[0007] Preferably, the nitrogen adsorption specific surface area is 0 m 2 / g or greater than 65m 2 / g or less. More preferably, the nitrogen adsorption specific surface area is 0 m 2 / g or more, 36m 2 / g or less. More preferably, the nitrogen adsorption specific surface area is 0 m 2 / g or greater, 32m 2 / g or less.
[0008] Preferably, the oil absorption is greater than 0 cc / 100g and less than 92 cc / 100g, more preferably greater than 0 cc / 100g and less than 80 cc / 100g.
[0009] Preferably, the carbon black satisfies the following condition (c): (c) the primary particle diameter is in the range of 45 nm to 70 nm, and more preferably, the primary particle diameter is in the range of 50 nm to 70 nm.
[0010] Preferably, the carbon black satisfies the following condition (d): (d) the particle size of the aggregates is in the range of 120 nm to 550 nm, and more preferably, the particle size of the aggregates is in the range of 120 nm to 400 nm.
[0011] Preferably, the carbon black satisfies the following condition (e): (e) the volatile matter content is 1% by weight to 5% by weight.
[0012] Preferably, the carbon black satisfies the following condition (f): (f) the resistivity is 0.020 Ω*cm or more.
[0013] The present disclosure further provides a sealant comprising a resin, a curing agent, and the carbon black described above.
[0014] Preferably, the sealant includes an antifoaming agent.
[0015] Preferably, the sealant is an electronic potting adhesive.
[0016] The present disclosure further provides the use of the above carbon black for use in a sealant.
[0017] Preferably, the sealant is an electronic potting adhesive. Effect of the Invention
[0018] The present inventors have unexpectedly discovered that when carbon black satisfies certain conditions, not only is the insulating property of the carbon black powder itself improved, but also high insulating properties can be exhibited when applied to a sealant. [Brief description of the drawings]
[0019] [Figure 1A] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 1. [Figure 1B] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 1. [Figure 1C] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 1. [Figure 1D] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 1. [Figure 2A] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 2. [Figure 2B] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 2. [Figure 2C] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 2. [Figure 3A] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Comparative Example 1. [Figure 3B] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Comparative Example 1. [Figure 3C]1 is a transmission electron microscope (TEM) photograph of the carbon black of Comparative Example 1. [Figure 4A] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 1. [Figure 4B] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 1. [Figure 4C] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 1. [Figure 5A] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 2. [Figure 5B] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 2. [Figure 5C] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 2. [Figure 5D] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 2. [Figure 5E] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 2. [Figure 5F] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Production Example 2. [Figure 6A] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Comparative Example 1. [Figure 6B] 1 is a transmission electron microscope (TEM) photograph of the carbon black of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Detailed Description of the Embodiments In this disclosure, "between X and Y" is synonymous with "from X to Y" and includes the end values X and Y.
[0021] The carbon black provided by the present disclosure satisfies the following conditions (a) and (b):
[0022] Condition (a): Nitrogen adsorption specific surface area (NSA) is 0 m 2 / g or greater, 130m2 In some embodiments, the nitrogen adsorption specific surface area is 0 m 2 / g or greater than 65m 2 In some embodiments, the nitrogen adsorption specific surface area is greater than 0 m2 / g and less than 40 m 2 In some embodiments, the nitrogen adsorption specific surface area is 0 m 2 / g or more, 36m 2 In some embodiments, the nitrogen adsorption specific surface area is 0 m 2 / g or greater, 32m 2 In some embodiments, the nitrogen adsorption specific surface area is 5, 10, 15, 20, 25, and 30 m 2 / g (between X and Y above).
[0023] Condition (b): Oil absorption (OAN) is greater than 0 cc / 100g and less than or equal to 95 cc / 100g. In some embodiments, oil absorption is greater than 0 cc / 100g and less than or equal to 92 cc / 100g. In some embodiments, oil absorption is greater than 0 cc / 100g and less than or equal to 80 cc / 100g. In some embodiments, oil absorption is between any two of the following values: 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, and 77 cc / 100g.
[0024] The carbon black may further satisfy the following condition (c):
[0025] Condition (c): The primary particle size is 45 to 70 nm. In some embodiments, the primary particle size is 50 to 70 nm.
[0026] The carbon black may further satisfy the following condition (d):
[0027] Condition (d): The particle size of the aggregates is in the range of 120 to 550 nm In some embodiments, the particle size of the aggregates is in the range of 120 to 400 nm.
[0028] In some embodiments, the carbon black satisfies the following conditions: NSA is 32 to 40 m 2 / g, OAN is 85 to 95 cc / 100 g, primary particle size is 45 to 65 nm, and aggregate particle size is 200 to 550 nm.
[0029] In some embodiments, the carbon black satisfies the following conditions: NSA is 20 to 32 m 2 / g, OAN is 70-85cc / 100g, primary particle size is 50-70nm, and aggregate particle size is 120-400nm.
[0030] The carbon black may further satisfy condition (e) below.
[0031] Condition (e): the volatile content is in the range of 1% to 5% by weight. In some embodiments, the volatile content is between any two of 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3.5%, 4.0%, and 4.5% by weight. In some embodiments, the volatile content is in the range of 1.3% to 3% by weight.
[0032] The carbon black may further satisfy the following condition (f):
[0033] Condition (f): The resistivity is 0.020 Ω*cm or more, for example, 0.020 to 0.060 Ω*cm. In some embodiments, the resistivity is 0.022 Ω*cm or more. In some embodiments, the resistivity is 0.024 Ω*cm or more.
[0034] The present disclosure also provides a sealant comprising a resin, a curing agent, and the aforementioned carbon black. The resin is well known to those skilled in the art to which the present disclosure pertains, and includes, but is not limited to, epoxy resin (such as bisphenol A epoxy resin, bisphenol F epoxy resin), polyurethane, and organosilicon. Examples of curing agents are well known to those skilled in the art to which the present disclosure pertains, and will not be described in detail herein.
[0035] The sealant may further include an antifoaming agent, including but not limited to BYK 1760, BYK A530, BASF SI2008, etc. The antifoaming agents may be used alone or in combination.
[0036] The present disclosure further provides the use of the above carbon black for use in a sealant.
[0037] In some embodiments, the sealant is an electronic potting adhesive.
[0038] [Manufacturing example: Carbon black manufacturing] The carbon blacks of Preparation Examples 1 and 2 are prepared by modifying N774 carbon black and N660 carbon black using the carbon material post-modification processing system disclosed in Taiwan Patent No. I796678. The preparation conditions are as shown in Table 1. The contents of Taiwan Patent No. I796678 are incorporated herein by reference in their entirety.
[0039] [Table 1]
[0040] Table 2 shows the nitrogen adsorption specific surface area (NSA), carbon black oil absorption (OAN), resistivity and volatile matter content of the carbon black powders themselves of Production Example 1, Production Example 2 and Comparative Example 1. Comparative Example 1 in Table 2 uses a commercially available carbon black. The measurement items listed in Table 2 were performed as follows.
[0041] [NSA (Nitrogen Adsorption Specific Surface Area)] The specific surface area of carbon black is measured according to ASTM D6556. The gas pressure of the gas adsorbed and desorbed on the surface and pores of carbon black at a constant temperature is measured according to the BET theory, using the nitrogen surface area as the total surface area of the external and internal surfaces. The specific surface area is calculated using the cross-sectional area of the gas molecule, the volume of the gas molecule and the sample weight.
number
[0042] [OAN (oil absorption number)] The OAN of carbon black is measured according to ASTM D2414. A quantitative amount of carbon black is weighed and the density is 1.042-1.047g / cm 3 Titrate to the end point with 100% white mineral oil. Calculate the absorbency value based on the weight of the carbon black sample and the titration volume, then substitute into the following equation to obtain the OAN value:
number
[0043] [Resistivity] A fixed amount of carbon black is weighed using a powder impedance measuring device PRCD2100 (manufactured by IEST), a pressure of 10 to 200 MPa is continuously applied, the pressure is maintained for 10 seconds, and the powder impedance is measured.
[0044] [Volatile content] The amount of organic compounds released by baking carbon black at 950°C for 7 minutes, such as residual oil, adhesives, and surface functional groups, can be measured, and the loss rate can be calculated by measuring the weight of the crucible before and after baking the carbon black.
[0045] [Table 2]
[0046] From the results in Table 2, the carbon blacks of Production Examples 1 and 2 had an NSA of 130 m 2 It can be seen that excellent resistivity can be obtained by setting the NSA to less than 95cc / 100g and the OAN to less than 95cc / 100g. To obtain even better resistivity, the NSA and OAN can be further reduced.
[0047] 1A, 1B, 1C, and 1D are transmission electron microscope (TEM) photographs taken at different positions of the carbon black of Production Example 1. As shown in Fig. 1A, 1B, 1C, and 1D, the primary particle diameters of the carbon black of Production Example 1 are 65 nm, 68 nm, 58 nm, 59 nm, and 61 nm, which are between 50 nm and 70 nm.
[0048] Figures 2A, 2B, and 2C are transmission electron microscope (TEM) photographs taken at different positions of the carbon black of Production Example 2. As shown in Figures 2A, 2B, and 2C, the primary particle diameters of the carbon black of Production Example 2 are 56.9 nm, 50.8 nm, 56.3 nm, 49.0 nm, 50.6 nm, 60.6 nm, 48.8 nm, 63.1 nm, 61.3 nm, and 55.2 nm, which are between 45 nm and 65 nm.
[0049] Figures 3A, 3B, and 3C are transmission electron microscope (TEM) photographs taken at different positions of the carbon black of Comparative Example 1. As shown in Figures 3A, 3B, and 3C, the primary particle sizes of the carbon black of Comparative Example 1 are 55 nm, 42 nm, and 54 nm.
[0050] Figures 4A, 4B, and 4C are transmission electron microscope (TEM) photographs taken at different positions of the carbon black of Production Example 1. As shown in Figures 4A, 4B, and 4C, the particle sizes of the aggregates of the carbon black of Production Example 1 are 248 nm, 264 nm, and 196.7 nm, which are between 120 nm and 400 nm.
[0051] 5A, 5B, 5C, 5D, 5E, and 5F are transmission electron microscope (TEM) photographs taken at different positions of the carbon black of Production Example 2. As shown in Fig. 5A, 5B, 5C, 5D, 5E, and 5F, the particle sizes of the aggregates of the carbon black of Production Example 2 are 251.3 nm, 504.8 nm, 244.3 nm, 434.5 nm, 443.5 nm, and 525.4 nm, which are between 200 nm and 550 nm.
[0052] 6A and 6B are transmission electron microscope (TEM) photographs taken at different positions of the carbon black of Comparative Example 1. As shown in Fig. 6A and 6B, the particle sizes of the aggregates of the carbon black of Comparative Example 1 are 333 nm and 371 nm, which are between 300 nm and 550 nm.
[0053] Example: Manufacturing of Electronic Potting Adhesive The carbon blacks of Production Example 1, Production Example 2, and Comparative Example 1 were mixed according to the components and ratios listed in Table 3 to prepare the electronic potting adhesives of Example 1 (electronic potting adhesive containing the carbon black of Production Example 1), Example 2 (electronic potting adhesive containing the carbon black of Production Example 2), and Comparative Example 2 (electronic potting adhesive containing the carbon black of Comparative Example 1), respectively.
[0054] [Table 3]
[0055] The electronic potting adhesives of Example 1, Example 2, and Comparative Example 2 were poured into a mold and heated in an oven at 80°C for 1 hour to obtain a test sample. After cooling, the film thickness was measured using a film thickness meter (C2401A01 manufactured by Covina), and the volume resistance was measured using a high insulation resistance meter (SM7120 manufactured by HIOKI), and the volume resistivity was calculated using the following formula. The results are shown in Table 4. Volume resistivity (Ω*cm) = resistance value (measured value, unit Ω) × 19.6 ÷ film thickness (cm)
[0056] [Table 4]
[0057] As shown in Table 4, the cured films formed by the electronic potting adhesives of the present disclosure have excellent volume resistivity, which means that the cured films have excellent insulating properties.
[0058] In summary, the present disclosure provides a method for obtaining highly insulating carbon black by limiting the carbon black to specific conditions. When this carbon black is used in a sealant, the sealant can also have high insulating properties.
[0059] However, the above is merely a preferred embodiment of the present disclosure and cannot be used to limit the scope of the present disclosure, that is, all simple equivalent changes and modifications made based on the claims and specifications of the present disclosure are within the scope of the claimed invention.
[0060] (Additional Note) (Appendix 1) Conditions (a) and (b) below: (a) Nitrogen adsorption specific surface area (NSA) is 0 m 2 / g or greater, 130m 2 / g or less, (b) The oil absorption rate is greater than 0cc / 100g and less than or equal to 95cc / 100g; Meet carbon black.
[0061] (Appendix 2) Nitrogen adsorption specific surface area is 0m 2 / g or greater than 65m 2 / g or less.
[0062] (Appendix 3) Nitrogen adsorption specific surface area is 0m 2 / g or more, 36m 2 / g or less.
[0063] (Appendix 4) Nitrogen adsorption specific surface area is 0m 2 / g or greater, 32m 2 / g or less.
[0064] (Appendix 5) 2. The carbon black according to claim 1, having an oil absorption of more than 0 cc / 100 g and less than or equal to 92 cc / 100 g.
[0065] (Appendix 6) 6. The carbon black according to claim 5, having an oil absorption of more than 0 cc / 100 g and less than or equal to 80 cc / 100 g.
[0066] (Appendix 7) Furthermore, if condition (c) (c) the primary particle size is in the range of 45 nm to 70 nm; The carbon black described in Appendix 1, which satisfies the above.
[0067] (Appendix 8) 8. The carbon black according to claim 7, having a primary particle size in the range of 50 nm to 70 nm.
[0068] (Appendix 9) Furthermore, the following condition (d) (d) the particle size of the aggregate is in the range of 120 nm to 550 nm; The carbon black described in Appendix 1, which satisfies the above.
[0069] (Appendix 10) 10. The carbon black according to claim 9, wherein the particle size of the aggregates is in the range of 120 nm to 400 nm.
[0070] (Appendix 11) Furthermore, the following condition (e) (e) a volatile content of 1% by weight to 5% by weight; The carbon black described in Appendix 1, which satisfies the above.
[0071] (Appendix 12) Furthermore, the following condition (f) (f) resistivity is 0.020 Ω*cm or more; The carbon black described in Appendix 1, which satisfies the above.
[0072] (Appendix 13) A sealant comprising a resin, a curing agent, and the carbon black described in appendix 1.
[0073] (Appendix 14) 14. The sealant of claim 13, further comprising an antifoaming agent.
[0074] (Appendix 15) 14. The sealant of claim 13, which is an electronic potting adhesive.
[0075] (Appendix 16) 2. Use of carbon black as described in Appendix 1 for use in sealants.
[0076] (Appendix 17) 17. The use of claim 16, wherein the sealant is an electronic potting adhesive.
Claims
1. The following conditions (a) and (b) (a) Nitrogen adsorption specific surface area (NSA) is 0 m 2 / g or more, 130m 2 / g or less, (b) The oil absorption capacity is greater than 0 cc / 100 g and less than or equal to 95 cc / 100 g; Carbon black meets the needs of the consumer.
2. Nitrogen adsorption specific surface area is 0m 2 / g or more, 65m 2 2. The carbon black according to claim 1, wherein the molecular weight of the carbon black is 1 / g or less.
3. Nitrogen adsorption specific surface area is 0m 2 / g or more, 36m 2 3. The carbon black according to claim 2, having a molecular weight of 1:1 or less.
4. Nitrogen adsorption specific surface area is 0m 2 / g or more, 32m 2 4. The carbon black according to claim 3, wherein the molecular weight of the carbon black is 1 / g or less.
5. 2. The carbon black according to claim 1, having an oil absorption of more than 0 cc / 100 g and not more than 92 cc / 100 g.
6. 6. The carbon black according to claim 5, having an oil absorption of more than 0 cc / 100 g and not more than 80 cc / 100 g.
7. Furthermore, the following condition (c) (c) the primary particle size is in the range of 45 nm to 70 nm; The carbon black according to claim 1 ,
8. The carbon black according to claim 7, having a primary particle size in the range of 50 nm to 70 nm.
9. Furthermore, the following condition (d) (d) the particle size of the aggregate is in the range of 120 nm to 550 nm; The carbon black according to claim 1 ,
10. The carbon black according to claim 9, wherein the particle size of the aggregates is in the range of 120 nm to 400 nm.
11. Furthermore, the following condition (e) (e) a volatile content of 1% to 5% by weight; The carbon black according to claim 1 ,
12. Furthermore, the following condition (f) (f) resistivity is 0.020 Ω*cm or more; The carbon black according to claim 1 ,
13. 10. A sealant comprising a resin, a curing agent, and the carbon black of claim 1.
14. 14. The sealant of claim 13 further comprising an antifoaming agent.
15. 14. The sealant of claim 13 which is an electronic potting adhesive.
16. 2. Use of the carbon black according to claim 1 in a sealant.
17. The use of claim 16, wherein the sealant is an electronic potting adhesive.
Citation Information
Patent Citations
Resin composition, and electronic part and piezoelectric ceramic part coated therewith
JP1996109315A
Carbon black for ink
JP2001207080A
Epoxy resin composition for sealing and electronic part device
JP2001302885A
Intermediate transfer body and image forming device
JP2001324880A
Carbon black, black composition and production method for carbon black
JP2004075985A